Reducing PTSD symptoms through unconscious intervention - Qing Yang; Yingying Wang; Chunyu Liu; Pu Zhi; Siyu Chen; Yangyang Lei; Fei Xue; Zijian Zhu (Proceedings of the National Academy of Sciences, 2026)
Intrusive traumatic memories are a hallmark symptom of posttraumatic stress disorder (PTSD). Conventional therapies typically require explicit and emotionally distressing reexposure to trauma cues, often leading to high dropout rates among severely affected patients. This study examined whether trauma memory intrusions could be effectively reduced through unconscious intervention, minimizing emotional distress by subliminally presenting trauma-related visual cues during bilateral eye movement intervention, a core component of eye movement desensitization and reprocessing. Four experiments tested this approach: two utilizing an analogue trauma paradigm in healthy participants (N = 164), one clinical study with PTSD patients (N = 60), and one supplementary experiment in a subclinical sample (N = 30). Results demonstrated that this unconscious intervention significantly reduced the frequency of intrusive memories and effectively alleviated PTSD symptoms, with the frequency of intrusion decreasing by 56% and lasting at least 2 mo in PTSD patients. Critically, patients previously unable to tolerate conventional exposure therapy became capable of consciously confronting trauma cues postintervention. This unconscious intervention approach is brief (under 2 h total), minimally distressing, and requires limited patient disclosure, offering a promising alternative or adjunct to traditional trauma-focused treatments. It may substantially enhance treatment accessibility and tolerability for severely traumatized individuals otherwise unable to engage with traditional therapies.